Study of rs7759938, rs314280, and rs314276 Polymorphisms of LIN28B in Relation to Age at Menarche in Girls of Greek Descent - Vasiliki Rengina Tsinopoulou; Flora Bacopoulou; Liana Fidani; Dimitrios Dimitriadis; Spyridon Gerou; Athanasios Christoforidis (MDPI AG, 2024)
Background: Single-nucleotide polymorphisms in LIN28B, critical regulators of female growth and puberty, have been linked to age at menarche. Methods: We assessed the association of rs7759938, rs314280, and rs314276 with menarcheal age in girls of Greek descent. We reviewed the records of 248 girls who had their first menstruation before 18 years and who attended the Greek Departments of Pediatric Endocrinology from January 2021 to July 2023. Genotyping was performed by standard DNA-based methods. Association analyses involved both parametric and non-parametric tests. Results: The average age of breast and pubic hair development was 9.95 years, and the age at menarche was 11.55 years. Menarche occurred ≤11 years (mean 10.24 years) in 108 girls (43.5%) and >11 years (mean 12.55 years) in 140 (56.5%). The girls' menarcheal age correlated significantly with that of their mothers (average 12.1 years, p-value < 0.0001, Spearman's r 0.350). The dominant rs7759938(TT) genotype was the most common (55.2%), followed by the dominant rs314276(CC) (53.2%) and dominant rs314280(TT) (14.5%) genotypes. Conclusions: There was no association between age at menarche and any of the polymorphism genotypes/alleles or between genotypes/alleles and birth weight, gestational week, mode of delivery, and maternal age at menarche. Future large sample studies are warranted to confirm these results.